(untitled) (Web of Teachers: Inderscience Research, 2026)
This study explores the linguistic strategies of humor in Russian and Uzbek children’s prose, focusing on the ways in which humor is constructed, conveyed, and perceived within different cultural and linguistic frameworks. The research analyzes lexical, stylistic, and pragmatic devices such as wordplay, irony, exaggeration, repetition, and culturally specific references that contribute to humorous effects in children’s literature. Particular attention is given to how authors adapt humor to the cognitive and emotional development of young readers, ensuring accessibility and engagement. The comparative approach highlights both universal and culture-specific features of humor in Russian and Uzbek texts. While Russian children’s prose often employs satire, absurdity, and linguistic playfulness, Uzbek children’s literature tends to emphasize moral didacticism, situational humor, and folklore-based comic elements. The study also considers the role of linguistic economy, narrative structure, and dialogic interaction in enhancing humor.